Determinants of Homonym and Synonym Rates of Record Linkage in Disease Registration - Brenner, H.; Schmidtmann, I. (Methods of Information in Medicine, 1996)
Reliable record linkage is an essential component of the quality of population-based disease registration. Quality assessment of disease registries should, therefore, include quantitative approaches to describe the extent of record-linkage errors. The homonym and synonym rates have been proposed for this purpose. The homonym rate quantifies the proportion of distinct patients excluded from registration due to erroneous linkage with other patients. The synonym rate quantifies the proportion of unrecognized duplicate notifications on patients already registered in the registry. This paper provides an algebraic assessment of the determinants of both rates. It is shown how the homonym and the synonym rate are determined by the discriminating power provided by the personal identifiers and the record linkage procedure on the one hand and the specific circumstances of disease registration on the other hand, such as the number of patients in the registry or the number of notifications per case. All these factors should be taken into account when reporting and interpreting results of record-linkage studies, particularly if comparisons are made between the performance of record-linkage procedures in different environments.
Keywords: Disease Registry; Homonym Rate; Record Linkage; Synonym Rate